Induction of erythropoietin gene expression in epithelial cells by chemicals identified in GATA inhibitor screenings. (18th October 2017) - Kaneko, Hiroshi; Katoh, Takehide; Hirano, Ikuo; Hasegawa, Atsushi; Tsujita, Tadayuki; Yamamoto, Masayuki; Shimizu, Ritsuko
Abstract : Erythropoietin (EPO) is a hormone that promotes proliferation, differentiation and survival of erythroid progenitors. EPO gene expression is regulated in a tissue‐specific and hypoxia‐inducible manner and is mainly restricted to renal EPO‐producing cells after birth. Chronic kidney disease (CKD) confers high risk for renal anemia due to lower EPO production from injured kidneys. In transgenic reporter lines of mice, disruption of a GATA‐binding motif within the Epo gene promoter‐proximal region restores constitutive reporter expression in epithelial cells. Here, mitoxantrone and its analogues, identified as GATA factor inhibitors through high‐throughput chemical library screenings, markedly induce EPO / Epo gene expression in epithelium‐derived cell lines and mice regardless of oxygen levels. In contrast, mitoxantrone interferes with hypoxia‐induced EPO gene expression in Hep3B cells. Cryptic promoters are created for the EPO / Epo gene expression in epithelial cells upon mitoxantrone treatment, and consequently, unique 5′‐untranslated regions are generated. The mitoxantrone‐induced aberrant transcripts contribute to the reporter protein production in epithelial cells that carry the reporter gene in the proper reading frame of mouse Epo gene. Thus, EPO production in uninjured adult epithelial cells may be a therapeutic approach for renal anemia in patients with CKD. Abstract : Mitoxantrone and its analogues markedly induce EPO/Epo gene expression in epithelium‐derived cell lines and mice regardless of oxygen levels. EPO production in uninjured adult epithelial cells may be a therapeutic approach for renal anemia in patients with CKD.